2014
DOI: 10.1021/jp503997t
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions of Amorphous Solid Acetone in Confined Geometry Investigated by Reflection Absorption Infrared Spectroscopy

Abstract: We investigated the phase transformations of amorphous solid acetone under confined geometry by preparing acetone films trapped in amorphous solid water (ASW) or CCl4. Reflection absorption infrared spectroscopy (RAIRS) and temperature-programmed desorption (TPD) were used to monitor the phase changes of the acetone sample with increasing temperature. An acetone film trapped in ASW shows an abrupt change in the RAIRS features of the acetone vibrational bands during heating from 80 to 100 K, which indicates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…Isothermal time-dependent RAIR spectra of 150 MLs of pure acetone (Figure S1), measured at different temperatures (115, 120, and 125 K), showed a major feature at ∼1718 cm −1 due to bulk acetone. 49,55,56 This confirmed that the 1721 cm −1 peak is entirely a new feature and arises only because of acetone hydrate and not because of bulk acetone or its aggregates. Temperature-dependent RAIR spectra shown in Figure S2 suggest that acetone hydrate starts to form at 130 K. However, it is not stable in this condition and dissociated within 3 h. The inset of Figure 1 shows the reduction of C=O stretching band with time and resulted in a weak feature at ∼1702 cm −1 .…”
supporting
confidence: 57%
See 2 more Smart Citations
“…Isothermal time-dependent RAIR spectra of 150 MLs of pure acetone (Figure S1), measured at different temperatures (115, 120, and 125 K), showed a major feature at ∼1718 cm −1 due to bulk acetone. 49,55,56 This confirmed that the 1721 cm −1 peak is entirely a new feature and arises only because of acetone hydrate and not because of bulk acetone or its aggregates. Temperature-dependent RAIR spectra shown in Figure S2 suggest that acetone hydrate starts to form at 130 K. However, it is not stable in this condition and dissociated within 3 h. The inset of Figure 1 shows the reduction of C=O stretching band with time and resulted in a weak feature at ∼1702 cm −1 .…”
supporting
confidence: 57%
“…Taking the area under the 1721 cm –1 peak, the amount of acetone in the hydrate form was estimated to be 32.59% of the total acetone. Isothermal time-dependent RAIR spectra of 150 MLs of pure acetone (Figure S1), measured at different temperatures (115, 120, and 125 K), showed a major feature at ∼1718 cm –1 due to bulk acetone. ,, This confirmed that the 1721 cm –1 peak is entirely a new feature and arises only because of acetone hydrate and not because of bulk acetone or its aggregates. Temperature-dependent RAIR spectra shown in Figure S2 suggest that acetone hydrate starts to form at 130 K.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…The Journal of Physical Chemistry C Article 1709 cm −1 rather than at 1708 cm −1 as assigned in the previous work, 27 to achieve a better fit. However, this amount of difference is not physically meaningful.…”
Section: Discussionmentioning
confidence: 84%
“…Highly sensitive and selective techniques are required to probe buried layers and interfaces that can be found in the natural environment as well as in manufactured systems, where specific reaction mechanisms and transport processes occur that are still only partially understood. For instance, electrochemical and catalytic reactions, transport within the lipid bilayer of the cell, ,,, and partition of solutes in multiphase fluids ,, can be understood by scrutinizing precisely interfaces and buried molecular layers where these phenomena take place. , Conventional in situ and non-invasive methods such as sum frequency generation (SFG), ,,, Fourier transform infrared (FTIR) spectroscopy, , ,, grazing incidence X-ray diffraction (GIXD), and Raman spectroscopy , have been applied to improve our understanding of these processes. , Despite the high selectivity of SFG and GIXD for interfaces, they lack the capacity to investigate the bulk of buried molecular layers. As for the usual methodologies and techniques relying on FTIR and Raman spectroscopy, they are commonly found to have a poor surface sensitivity or to be unselective to the depth profile of multilayer systems.…”
Section: Introductionmentioning
confidence: 99%